Android Quick Browser - Kothakapu, Aravind Reddy (Kansas State University, 2016)
People are more inclined to use mobiles instead of other computing devices like desktops and laptops due to their portability and ease of use. A number of desktop applications have become available as mobile applications in response to the increasing market demand. Android is one of the largest and most popular open source platforms that offers developers complete access to framework APIs in order to develop innovative mobile applications The objective of this project was to develop an Android application for daily users of Android mobiles. This application advantageously allows users to search the internet on their phone, save preferred links, and prioritize outputs based on saved links. The application uses the Google search engine as its primary search engine and customizes links for the user.
Keywords: Android